Grid Connected Distributed Generation System with High Voltage Gain Cascaded DC-DC Converter Fed Asymmetric Multilevel Inverter Topology - S. Nagaraja Rao; D. V. Ashok Kumar; Ch. Sai Babu (Institute of Advanced Engineering and Science, 2018)
The paper presents distributed generation (DG) system in grid connected mode of operation with asymmetric multi-level inverter (AMLI) topology. Cascaded type DC-DC converter is employed to feed proposed AMLI topology. The DG output voltage (generally low voltage) is stepped up to the required level of voltage using high-gain DC-DC converter. Proposed AMLI topology consists of capacitors at the primary side. The output of high-gain DC-DC converter is fed to split voltage balance single-input multi-output (SIMO) circuit to maintain voltage balance across capacitors of AMLI topology. Cascaded DC-DC converters (both high-gain converter and SIMO circuit) are operated in closed-loop mode. The proposed AMLI feeds active power to grid converting DC type of power generated from DG to AC type to feed the grid. PWM pattern to trigger power switches of AMLI is also presented. The inverting circuit of MLI topology is controlled using simplified Id-Iq control strategy in this paper. With the proposed control theory, the active power fed to grid from DG is controlled and power factor is maintained at unity. The proposed system of DG integration to grid through cascaded DC-DC converters and AMLI structure is validated from fixed active power to grid from DG condition. The proposed system is developed and results are obtained using MATLAB/SIMULINK software.